Willingness To Pay Masyarakat dalam Mengurangi Dampak Sampah Rumah Tangga - Sulistya Rini Pratiwi; Kasmawati Kasmawati (Jurnal Ekonomi Pembangunan, 2019)
The purpose of this study is to analyze the willingness to pay in the City of Tarakan. Its aim focuses on reducing the negative impact of waste and determine how much influence the value of the willingness to pay the community in reducing the harmful effects of waste in the City of Tarakan. The type of data used in the study is primary data and secondary data. The research location was carried out in four sub-districts in Tarakan City, the research took 30 days to distribute questionnaires, and 400 respondents were received in four sub-districts. City of Tarakan in the amount of Rp. 16575. Simultaneous test results showed that the independent variables namely age, sex, level of education, number of family members and income affect WTP (willingness to pay the community).